Prediction of emergence agitation using withdrawal reaction following rocuronium injection in preschool-aged patients undergoing inguinal herniorrhaphy: a preliminary exploratory observational trial - Kim DH; Roh GU; Lee YB; Choi CI; Lee JM; Chae YJ (Dove Medical Press, 2018)
Dae Hee Kim,1 Go Un Roh,2 Young Bok Lee,3 Chang Ik Choi,3 Jae Moon Lee,3 Yun Jeong Chae1 1Department of Anesthesiology and Pain Medicine, Ajou University School of Medicine, Suwon, 2Department of Anesthesiology and Pain Medicine, CHA Bundang Medical Center, CHA University, Seongnam, 3Department of Anesthesiology and Pain Medicine, Yonsei University Wonju College of Medicine, Wonju, Republic of Korea Purpose: The development of emergence agitation (EA) is associated with several factors including age, preoperative anxiety, postoperative pain, anesthesia method, and surgery type. No studies have investigated whether the withdrawal reaction following rocuronium injection can predict the occurrence of EA. Therefore, we investigated this relationship in preschool-aged children undergoing inguinal herniorrhaphy, and which grade of withdrawal reaction is appropriate for identifying patients at risk of experiencing EA. Methods: A total of 40 patients were enrolled in this study. During anesthesia induction, the withdrawal reaction after loss of consciousness following rocuronium injection was assessed using a 4-point scale. After surgery, EA was assessed using the Watcha scale. Results: There was a correlation between withdrawal reaction and EA on admission to the postanesthesia care unit (PACU). Patients with a severe withdrawal reaction (grade 3) showed a significantly higher incidence of severe EA requiring medication on admission to the PACU. Conclusion: The findings of this preliminary exploratory observational study suggest that it is possible for withdrawal movement following rocuronium injection during anesthesia induction to reflect pain sensitivity of pediatric patients, which in turn may be useful in identifying those at risk of severe EA on admission to the PACU among preschool children undergoing inguinal herniorrhaphy. Further studies with a larger sample size are required to validate these findings. The exact correlation between pain reaction following rocuronium injection and postoperative pain or pain-related phenomenon should be elucidated. Keywords: emergence agitation, prediction, rocuronium, withdrawal movement